STIEGLER, FOUCAULT, AND EPICTETUS: THE THERAPEUTICS OF READING AND WRITING. - Lampe, Kurt (Symposium: Canadian Journal of Continental Philosophy / Revue Canadienne de Philosophie Continentale)
Why does Bernard Stiegler speak of "this culture, which I have named, after Epictetus, my meletef" In the first part of this article, I elucidate Stiegler's claims about both Stoic exercises of reading and writing and their significance for the interpretive questions he has adapted from Michel Foucault and Jacques Derrida. In particular, I address the relations among care for oneself and others, the use of material technologies, and resistance to subjection or "freedom." In the second part, I consider the merits and limitations of Stiegler's comments about reading and writing in Stoicism, with particular attention to Epictetus. We will see that Stiegler's interpretive framework casts considerable light on ancient texts and contexts, on the condition that it be combined with close reading of ancient texts and engagement with specialist scholarship. Finally, in the conclusion, I will suggest that the history of technology in Epictetus's time contributes to a debate about Stiegler's theories.